Nicorandil attenuates cognitive impairment after traumatic brain injury via inhibiting oxidative stress and inflammation: Involvement of BDNF and NGF - Yaoyan Tu; Desen Han; Yanjun Liu; Dequan Hong; Rehua Chen (Brain and Behavior, 2024)
Abstract Background and purpose Cognitive impairment is a prevalent adverse consequence of traumatic brain injury (TBI). The neuroprotective effects of nicorandil (N‐(2‐hydroxyethyl)‐nicotinamide nitrate) has been previously documented, yet its protective effects against cognitive dysfunction post‐TBI remain unclear. Hence, the present study was aimed to evaluate whether nicorandil attenuates cognitive dysfunction in TBI rats and the underlying mechanism behind this process. Methods The TBI model was established with a controlled cortical impact (CCI). The effects of nicorandil on cognitive dysfunction of rats with TBI were examined through Novel object recognition (NOR) test, Y‐maze test, and Morris water maze (MWM) task. After behavioral tests, hippocampal tissue was collected for Quantitative real‐time PCR, Western blot analysis, and Enzyme‐linked immunosorbent assay (ELISA) assay. Results We observed that nicorandil administration effectively ameliorates learning and memory impairment in TBI rats. Alongside, nicorandil treatment attenuated oxidative stress in the hippocampus of TBI rats, characterized by the decreased reactive oxygen species generation, malondialdehyde, and protein carbonyls levels, and concurrent promotion of antioxidant‐related factors (including superoxide dismutase, glutathione peroxidase, and catalase) activities. Additionally, nicorandil treatment attenuated the inflammatory response in the hippocampus of TBI rat, as evidenced by the upregulated levels of interleukin (IL)‐1β, IL‐6, and tumor necrosis factor‐α (TNF‐α), as well as the downregulated level of IL‐10. Mechanistically, nicorandil treatment significantly enhanced the mRNA and protein levels of neurotrophic factors, brain‐derived neurotrophic factor (BDNF) and nerve growth factor (NGF) in the hippocampus of TBI rats. Conclusion These findings suggest that nicorandil mitigates cognitive impairment after TBI by suppressing oxidative stress and inflammation, potentially through enhancing BDNF and NGF levels.